Barriers to clinical trial enrollment of older adults with cancer: A qualitative study of the perceptions of community and academic oncologists. Issue 2 (March 2020) - Sedrak, Mina S.; Mohile, Supriya G.; Sun, Virginia; Sun, Can-Lan; Chen, Bihong T.; Li, Daneng; Wong, Andrew R.; George, Kevin; Padam, Simran; Liu, Jennifer; Katheria, Vani; Dale, William
Abstract: Objectives: Oncologists can be one of the major barriers to older adult's participation in research. Multiple studies have described academic clinicians' concerns for not enrolling older adults onto trials. Although the majority of older adults receive their cancer care in the community, few studies have examined the unique challenges that community oncologists face and how they differ from oncologist-related barriers in academia. Methods: Semi-structured interviews were conducted by telephone or face-to-face with 44 medical oncologists (24 academic-based and 20 community-based) at City of Hope from March to June 2018. Interviews explored oncologists' perceptions of barriers to clinical trial enrollment of older adults with cancer. Data were analyzed using qualitative content analysis. Results: Of the 44 participants, 36% were women and 68% were in practice for >10 years. Among the entire sample, stringent eligibility criteria (n = 20) and oncologist concerns for treatment toxicities (n = 15) were the most commonly cited barriers. Compared to academic oncologists, community oncologists more often cited patient attitudes, beliefs, and understanding (n = 9 vs. n = 2) and caregiver burden (n = 6 vs. n = 0). In contrast, compared to community oncologists, academic oncologists more often cited oncologist bias (n = 10 vs. n = 3) and insufficient time/support (n = 4 vs. n = 1). Conclusions: Differences in perceptions among academic and community oncologists about trials suggest that barriers are multifaceted, complex, and vary by practice setting. Interventions to increase trial accrual among older adults with cancer may benefit from being tailored to address the unique barriers of different practice settings.